ANOTHER NOTE ON PODOCONIS MEGASPERMA BOEDIJN (HYPHOMYCETES) - Mien A. Rifai (BRIN Publishing (Penerbit BRIN), 2008)
RIFAI, M.A. 2008. Another note on Podoconis megasperma Boedijn (Hyphomycetes). Reinwardtia 12 (4): 277– 279. –– Exosporium megaspermum (Boedijn) Rifai and Exosporium ampullaceum (Petch) M.B.Ellis are transferred to Neopodoconis Rifai, a newly created genus extracted from Exosporium Link based on the nature of the true septation of their rostrate conidia. Two new combinations, Neopodoconis ampullacea (Petch) Rifai and Neopodoconis megasperma (Boedijn) Rifai, accordingly are proposed.